56.1k views
5 votes
Rex, Paulo, and Ben are standing on shore watching for dolphins. Paulo sees one surface directly in front of him about a hundred feet away. Use the spaces provided below to prove that the square of the distance between rex and Ben and the dolphin, and Ben and the dolphin.

URGENT !! I NEED TO PASS THIS TO GRADUATE !!

Rex, Paulo, and Ben are standing on shore watching for dolphins. Paulo sees one surface-example-1
Rex, Paulo, and Ben are standing on shore watching for dolphins. Paulo sees one surface-example-1
Rex, Paulo, and Ben are standing on shore watching for dolphins. Paulo sees one surface-example-2
User NiravS
by
6.5k points

2 Answers

5 votes

Answer:

Given information:
\triangle ADC\sim \triangle ACB and
\triangle BDC\sim \triangle BCA.

To Prove :
a^2+b^2=c^2

Proof:

Statement Proof

1.
\triangle ADC\sim \triangle ACB 1. Given

2.
(AC)/(AB)=(AD)/(AC) 2. The ratio of corresponding parts of similar triangles is a constant

3.
(b)/(c)=(e)/(b) 3. Rewrite statement 2 using given side labels.

4.
b^2=ce 4. Cross multiply statement 4

5.
\triangle BDC\sim \triangle BCA 5. Given

6.
(BC)/(BA)=(BD)/(BC) 6. The ratio of corresponding parts of similar triangles is a constant

7.
(a)/(c)=(d)/(a) 7. Rewrite statement 5 using given side labels.

8.
a^2=cd 8. Cross multiply statement 7

9.
a^2+b^2=cd+ce 9. Add statement 4 and 8

10.
a^2+b^2=c(d+e) 10. c is common factor

11.
a^2+b^2=c^2 11. Segment addition property.

Hence proved.

User Lee Jacobs
by
5.8k points
0 votes

1.
m\angle BAC=m\angle CAD,\ m\angle ACB=m\angle ADC=90^(\circ), then
m\angle ABC=m\angle ACD and triangles ADC and ACB are similar by AAA theorem.


2. The ratio of the corresponding sides of similar triangles is constant, so



(AC)/(AB)= (AD)/(AC).


3. Knowing lengths you could state that
(b)/(c)= (e)/(b).


4. This ratio is equivalent to
b^2=ce.


5.
m\angle ABC=m\angle CBD,\ m\angle ACB=m\angle CDB=90^(\circ), then
m\angle BAC=m\angle BCD and triangles BDC and BCA are similar by AAA theorem.


6. The ratio of the corresponding sides of similar triangles is constant, so



(BC)/(BD)= (AB)/(BC).


7. Knowing lengths you could state that
(a)/(d)= (c)/(a).


8. This ratio is equivalent to
a^2=cd.


9. Now add results of parts 4 and 8:



b^2+a^2=ce+cd.


10. c is common factor, then:



b^2+a^2=c(e+d).


11. Since
e+d=c you have
a^2+b^2=c\cdot c=c^2.



User Abdul Basit Rishi
by
6.2k points